Improving Criminal Responsibility Determinations Using Structured Professional Judgment - Acklin, Marvin W.; Velasquez, Joseph P. (Frontiers in Psychology, 2021)
Forensic psychologists commonly utilize unstructured clinical judgment in aggregating clinical and forensic information in forming opinions. Unstructured clinical judgment is prone to evaluator bias and suboptimal levels of inter-rater reliability. This article proposes Structured Professional Judgment (SPJ) methods as a potential remedy. Following a review of canonical forensic assessment models, the prevalence of bias in forensic judgments, and inter-rater agreement in criminal responsibility (CR) determinations, this article presents a SPJ model for CR evaluations translated from violence risk assessment methodology. A systematic user-friendly methodology is described, applying procedural checklists, application of a mental state at time of the offense (MSO) model using structured data collection methods, aggregation of empirical evidence guidelines, and post-hoc hypothesis testing using the Analysis of Competing Hypotheses (ACH). A case study describes application of the procedural and CR decision model in a complex homicide case. The model demonstrates the power and efficacy of the application of SPJ to forensic decision-making and is relevant to other types of forensic assessment (e.g., competency to stand trial, post-acquittal release decision-making).